Interplay between reactive oxygen species and ERK activation in cervical cancer cells - Larrauri-Rodríguez, Karen Andrea; Leon-Chavez, Bertha Alicia; Vallejo-Ruiz, Verónica; Peña, Lourdes Millán-Perez; Maycotte, Paola (Frontiers in Cell and Developmental Biology, 2024)
IntroductionAmong the types of cancer affecting women, cervical cancer (CC) is a public health problem with high global incidence and mortality rates. It is currently classified into three main histological types: squamous cell carcinoma (SCC), adenocarcinoma (AC), and adenosquamous (ASC) carcinoma. All of them lack a targeted therapy. The primary risk factor for CC is Human Papilloma Virus (HPV) infection, which is known to increase reactive oxygen species (ROS), contributing to malignant transformation and tumor progression. At basal levels, ROS can function as second messengers in signaling pathways, and elevated concentrations have been linked to their overactivation. One of these, the ERK pathway, is implicated in both cell proliferation and differentiation and is often dysregulated in cancer, promoting malignant transformation. Several studies have proposed antioxidant supplementation or ERK inhibitors as potential therapies.MethodsIn vitro studies were performed using CC cell lines. ROS levels were evaluated by flow cytometry; cellular proliferation, death and migration were evaluated using real-time microscopy; cell viability was evaluated with crystal violet staining, and phosphorylated ERK levels were evaluated by Western Blot. A bioinformatic analysis was done in a cervical cancer database.ResultsWe elucidate part of the complex interplay between ROS and ERK pathway in CC pro-tumorigenic characteristics. Through bioinformatic analysis, we found distinct ROS and ERK activation patterns across CC tumor samples from different histological types. However, in vitro, ROS regulated migration and viability in CC, with no discernible variance based on histological classification. ERK activation, however, differed according to the histological type with SCC displaying increased ERK activation compared to AC and regulating cellular migration in SCC cells.DiscussionOur study identifies a potential synergistic interaction between ROS and ERK inhibitors, highlighting the therapeutic promise of combinatorial targeting for CC treatment. These findings underscore the importance of personalized approaches aimed at improving the outcomes of CC patients.